PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KETERAMPILAN PROSES IPA SISWA SDIT AL-MUMTAZ PONTIANAK - Faturrahman, Fachry; Rosnita, Rosnita; Kresna, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The aim of this study generally was to obtain information about  the effect of problem based learning models toward Precess Science skills (IPA) at AL-Mumtaz Islamic Integrated Elementary School  Pontianak . The method used in this research is the experimental method. The experimental research design in this study is Pre-experimental Design. The type of  it is One Group Pretest-Posttest Design. The sample in this study were all students of fiveth grade B elementary school. According data analyzed has been obtained the average of student post-test is 74.228. From data analyzed t-test has been yield  tcount  equal 10.313 and  ttable = 7.815. It means that 10.313 >7.185. In other words tcount >  ttable. The result indicated that Ho  rejected and Ha accepted. Then, according the calculation of  the effect size (ES) has obtained 0,992 in the criteria is high to the part of the way ES > 0.8. It can be concluded that there is significant effect in using of problem based learning models toward Science Process Skills of the student elementary school fiveth grade.  Key Words : Problem Based Learning and Science Process Skills